Local solutions for sustainable food systems: The contribution of orphan crops and wild edible species - Borelli, Teresa; Hunter, Danny; Padulosi, Stefano; Amaya, Nadezda; Meldrum, Gennifer; Oliveira Beltrame, Daniela Moura de; Samarasinghe, Gamini W.L.; Wasike, Victor W.; Güner, Birgül; Tan, Ayfer; Dembélé, Yara Koreissi; Lochetti, Gaia; et al. (MDPI, 2020)
Calls for a global food system transformation and finding more sustainable ways of producing healthier, safe and nutritious food for all have spurred production approaches such as sustainable intensification and biofortification with limited consideration of the copious amounts of orphan crops, traditional varieties and wild edible species readily available in many countries, mostly in and around smallholder farmers’ fields. This paper explores the potential role of locally available; affordable and climate-resilient orphan crops, traditional varieties and wild edible species to support local food system transformation. Evidence from Brazil, Kenya, Guatemala, India, Mali, Sri Lanka and Turkey is used to showcase a three-pronged approach that aims to: (i) increase evidence of the nutritional value and biocultural importance of these foods, (ii) better link research to policy to ensure these foods are considered in national food and nutrition security strategies and actions, and (iii) improve consumer awareness of the desirability of these alternative foods so that they may more easily be incorporated in diets, food systems and markets. In the seven countries, this approach has brought about positive changes around increasing community dietary diversity and increasing market opportunities for smallholder growers, as well as increased attention to biodiversity conservation.